2012
DOI: 10.1007/s00412-011-0358-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of genomic integrity

Abstract: Inefficient and inaccurate repair of DNA damage is the principal cause of DNA mutations, chromosomal aberrations, and carcinogenesis. Numerous multiple-step DNA repair pathways exist whose deployment depends on the nature of the DNA lesion. Common to all eukaryotic DNA repair pathways is the need to unravel the compacted chromatin structure to facilitate access of the repair machinery to the DNA and restoration of the original chromatin state afterward. Accordingly, our cells utilize a plethora of coordinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 204 publications
(283 reference statements)
0
32
0
6
Order By: Relevance
“…Recent studies have revealed that K63Ub synthesis is regulated by the deubiquitinating enzyme, OTUB1 (OTU domain-containing ubiquitin aldehyde-binding protein 1; Wiener et al, 2012). It is thought that RNF8 executed ubiquitination has a role in maintaining genomic integrity, however, the role of post-damage monoubiquitylation in chromatin reassembly needs to be elucidated (Deem et al, 2012). It has been reported that RNF8 is inactive toward nucleosomal histone H2A.…”
Section: Histone Ubiquitinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that K63Ub synthesis is regulated by the deubiquitinating enzyme, OTUB1 (OTU domain-containing ubiquitin aldehyde-binding protein 1; Wiener et al, 2012). It is thought that RNF8 executed ubiquitination has a role in maintaining genomic integrity, however, the role of post-damage monoubiquitylation in chromatin reassembly needs to be elucidated (Deem et al, 2012). It has been reported that RNF8 is inactive toward nucleosomal histone H2A.…”
Section: Histone Ubiquitinationmentioning
confidence: 99%
“…In addition to histones, non-histone proteins are also involved in developing special chromatin structures. The known histone modifications induced following ionizing radiation exposure are phosphorylation, acetylation, methylation, and ubiquitination (Pandita and Richardson, 2009;Deem et al, 2012). Among these major chromatin modifications, post-damage-induced histone phosphorylation has been the most thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“…The relaxed chromatin structure facilitates the activation and recruitment of the kinase ATM, which initiates a signaling cascade leading to histone acetylation and additional chromatin remodeling. These modifications at the DSB site promote amplification of the DDR, recruit repair factors, and provide accessibility to the repair machinery (Deem et al 2012). Following repair, acetylation of lysine 56 on histone H3 is required to inactivate the DDR (Chen and Tyler 2008) and to allow reassembly of nucleosomes at the repair site.…”
mentioning
confidence: 99%
“…In response to changing conditions during development or in the environment, post-translational protein modification can much more rapidly alter the activity of the proteome compared to transcriptional or translational control mechanisms 4,14,19-21 . While numerous protein modifications are known, for example histone methylation and acetylation, the most widely studied modification is phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Modified-protein-specific antibodies can be used in high-throughput RNAi screens 41 or to test hypotheses related to control of a signaling pathway or utilization of the phosphorylated protein 42-45 . Importantly, modified-protein-specific antibodies can be used to purify protein-protein, protein-DNA or protein-RNA complexes that contain the modified protein; a widely employed example is the use of antibodies specific to modified histones for analysis of genomic regions that contain the modified histone in chromatin 4,14,20,24,46,47 .…”
Section: Introductionmentioning
confidence: 99%